An improved staining protocol for the assessment of arbuscular mycorrhizal in bryophytes - Cottet, Agustina Celeste (2018)
The most accepted method for staining arbuscular mycorrhiza (AM) in vascular plants has been one proposed by Phillips & Hayman in 1970. In particular, for the study of AM in bryophytes (s.l.) [Anthocerotophyta, Bryophyta (s.s.), Marchantiophyta] some authors have introduced modifications tothis technique. Even though all these protocols stain AM, their main disadvantage is related to the result of material maceration (e.g. over-softening or completely destroying plant cells due to the high temperaturesused, the high concentrations of reagents or the long-term exposure to aggressive chemicals). In order to optimise the results for the observation of AM in this group of plants, a modification is presented to the traditional staining technique. In the protocol here proposed, 70% ethanol is used as fixative and first clarifier, 1% potassium hydroxide (KOH) (80 °C, 20 min) as a second clarifier; 1% hydrochloric acid (HCl) (50 °C, 10 min) as an acidifier and 0.05% trypan blue (60 °C, 20 min) for dyeing. This improved protocol is not destructive, it is fast to perform and it is of wide application since it allows staining the AM in bryophytes.